Radiation Induces Apoptosis and Osteogenic Impairment through miR-22-Mediated Intracellular Oxidative Stress in Bone Marrow Mesenchymal Stem Cells - Zhonglong Liu; Tao Li; Si'nan Deng; Shuiting Fu; Xiaojun Zhou; Yue He (Hindawi Limited, 2018)
Bone marrow mesenchymal stem cells (BMSCs) were characterized by their multilineage potential and were involved in both bony and soft tissue repair. Exposure of cells to ionizing radiation (IR) triggers numerous biological reactions, including reactive oxygen species (ROS), cellular apoptosis, and impaired differentiation capacity, while the mechanisms of IR-induced BMSC apoptosis and osteogenic impairment are still unclear. Through a recent study, we found that 6 Gy IR significantly increased the apoptotic ratio and ROS generation, characterized by ROS staining and mean fluorescent intensity. Intervention with antioxidant (NAC) indicated that IR-induced cellular apoptosis was partly due to the accumulation of intracellular ROS. Furthermore, we found that the upregulation of miR-22 in rBMSCs following 6 Gy IR played an important role on the ROS generation and subsequent apoptosis. In addition, we firstly demonstrated that miR-22-mediated ROS accumulation and cell injury had an important regulated role on the osteogenic capacity of BMSCs both in vitro and in vivo. In conclusion, IR-induced overexpression of miR-22 regulated the cell viability and differentiation potential through targeting the intracellular ROS.